Heritability of the Structures and 13C Fractionation in Tomato Leaf Wax Alkanes: A Genetic Model System to Inform Paleoenvironmental Reconstructions - Bender, Amanda L. D.; Chitwood, Daniel H.; Bradley, Alexander S. (Frontiers in Earth Science, 2017)
Leaf wax n-alkanes are broadly used to reconstruct paleoenvironmental information. However, the utility of n-alkanes as a paleoenvironmental proxy may be modulated by the extent to which biological as well as environmental factors influence the structural and isotopic variability of leaf waxes. In paleoclimate applications, there is usually an implicit assumption that most variation of leaf wax traits through a time series can be attributed to environmental change and that biological sources of variability within plant communities are small. For example, changes in hydrology affect the δ2H of waxes via rainwater and the δ13C of leaf waxes by changing plant communities. We measured the degree of genetic control over δ13C variation in leaf waxes within closely related species with an experimental greenhouse growth study. We measured the proportion of variability in structural and isotopic leaf wax traits that is attributable to genetic variation using a set of 76 introgression lines (ILs) between two interfertile Solanum (tomato) species: S. lycopersicum cv M82 (hereafter cv M82) and S. pennellii. Leaves of S. pennellii, a wild desert tomato relative, produced significantly more iso-alkanes than cv M82, a domesticated tomato cultivar adapted to water-replete conditions. We report a methylation index to summarize the ratio of branched (iso- and anteiso-) to total alkanes. Between S. pennellii and cv M82, the iso-alkanes were found to be enriched in 13C by 1.2–1.4‰ over n-alkanes. The broad-sense heritability values (H2) of leaf wax traits describe the degree to which genetic variation contributes to variation of these traits. Variation of individual carbon isotopic compositions of alkanes were of low heritability (H2 = 0.13–0.19), suggesting that most variation in δ13C of leaf waxes in this study can be attributed to environmental variance. This supports the interpretation that variation in the δ13C of wax compounds recorded in sediments reflects paleoenvironmental and vegetation changes. Average chain length (ACL) values of n-alkanes were of intermediate heritability (H2 = 0.30), suggesting that ACL values are more strongly influenced by genetic cues.